Comparative Analysis of Variational Autoencoder (VAE) and Generative Adversarial Network (GAN) Algorithms for image (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
Variational Autoencoder (VAE) and Generative Adversarial Network (GAN) are topics for developing generative algorithms for image creation, image reconstruction, and data augmentation. Â These two models are solutions to models with limited data by generating data. Even though both models generate data, the way they work is different. The VAE model can produce image variations by relying on latent distributions. In contrast, GANs are models consisting of two main parts, namely a generator and a discriminator, which compete to produce increasingly realistic images. This research aims to analyze the comparison of two image-generative approaches by showing the trade-off between image realism and variation in the context of VAE and GAN. Experimental results show that GAN tends to produce more realistic and sharp images, but VAE has the advantage of producing variations in the distribution of the resulting images.